1999
DOI: 10.2337/diabetes.48.3.557
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system effects of intranasally administered insulin during euglycemia in men.

Abstract: Insulin receptors have been detected in several structures of the brain, yet the biological significance of insulin acting on the brain remains rather unclear. In humans, direct central nervous effects of insulin are difficult to distinguish from alterations in neuronal functions because of insulin-induced decrease in blood glucose levels. Since several intranasally administered viruses, peptides, and hormones have been shown to penetrate directly from the nose to the brain, we tested whether insulin after int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 15 publications
9
92
0
1
Order By: Relevance
“…Also, prolonged treatment with insulin compounds did not affect immediate recall of words measured in session C (F(2,34) ¼ 0.01, p40.92 for main effect, Figure 2). Consistent with previous findings (Kern et al, 1999;Born et al, 2002) levels of plasma glucose and serum insulin were neither affected by acute nor by subchronic intranasal insulin administration (Table 1).…”
Section: Data Reduction and Analysissupporting
confidence: 92%
“…Also, prolonged treatment with insulin compounds did not affect immediate recall of words measured in session C (F(2,34) ¼ 0.01, p40.92 for main effect, Figure 2). Consistent with previous findings (Kern et al, 1999;Born et al, 2002) levels of plasma glucose and serum insulin were neither affected by acute nor by subchronic intranasal insulin administration (Table 1).…”
Section: Data Reduction and Analysissupporting
confidence: 92%
“…This study has been conducted with a conventional nasal spray atomizer filled with insulin formulated for subcutaneous delivery. The same group observed that insulin delivered intranasally improved memory and mood [40,53]. In addition, N2B delivered insulin decreased food intake and decreased postprandial serum insulin [54,55].…”
Section: Is N2b Insulin Appropriate As Therapy For Neurodegenerative mentioning
confidence: 76%
“…It should be mentioned that the study did not set out to evaluate the existence of this pathway. Kern et al (1999) evaluated whether nasally administered insulin affected the auditory evoked brain potential (AEP) measured during the performance of an oddball task in a study of 18 volunteers (double blind cross-over design). A dose of insulin (20 IU) or a placebo formulation was administered into the nasal cavity every 15 min for 60 min.…”
Section: Ratmentioning
confidence: 99%